The Role of University Libraries in Meeting Information Needs for Students and Lecturers: A Portrait of Libraries in North Sumatra - Muhammad Dalimunte; Kasron Nasution; Toguan Rambe (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This research was conducted in North Sumatra, by selecting three research locations altogether under the auspices of PTKIN (State Islamic Religious High School) namely the Library of North Sumatra UIN Medan, IAIN Padangsidimpuan and STAIN Mandailing Natal. The selection of this location was based on the representation of religious college libraries in North Sumatra. The three universities have different characteristics. This study aims to see a portrait of a university library in North Sumatra. The existence of a library is very vital in improving the academic quality of a university. The research model used is qualitative, by extracting in-depth data from the point of view of informants, through FGD (Focus Group Discussion), Observation and documentation studies. The results show that there are three roles of library managers in realizing an effective information service system in university libraries. North Sumatra, among others; providing guidance services to users (users), providing circulation services,